WORK-FAMILY CONFLICT AND SOURCES OF SUPPORT AMONGST MALAYSIAN DUAL-CAREER EMPLOYEES - Meera Komarraju , (Asian Academy of Management Journal, 2006)
As the number of dual-career employees entering the workplace increases, it is important to understand how the integration of work and family responsibilities influences work outcomes. The current study examined occupational role salience, work-family conflict, basic understandings, spousal support, and organizational support as predictors of work satisfaction. One hundred and sixteen dual-career faculty and staff from three Malaysian universities completed a survey questionnaire. Results from stepwise regression analyses showed that across all employees, work-family conflict was the most significant predictor of work satisfaction. More specifically, for male employees, spousal support was the most important predictor of work satisfaction followed by work-family conflict. Interestingly, for female employees, work-family conflict was the most significant predictor followed by organizational support. These results suggest that dual-career employees who find family responsibilities intruding into their work activities are likely to experience lesser work satisfaction. Dual-career employees receiving support and encouragement from a spouse or from the employing organization are more likely to experience increased work satisfaction.